The girl with all the gifts - Carey, Mike, 1959- (Orbit, 2015)
Not every gift is a blessing. Every morning, Melanie waits in her cell to be collected for class. When they come for her, Sergeant Parks keeps his gun pointing at her while two of his people strap her into the wheelchair. She thinks they don't like her. She jokes that she won't bite. But they don't laugh. Melanie is a very special girl. Emotionally charged and gripping from beginning to end, The girl with all the gifts is the most powerful and affecting thriller you will read this year.